FROM PROFESSIONAL DEVELOPMENT TO PROFESSIONAL LEARNING: A PERSONALIZED APPROACH FOR TEACHERS - Askew, Abbey L (East Carolina University, 2021)
Improvement of teacher quality has been identified as a strong factor for improving student learning and increasing student achievement. Developing teacher knowledge and pedagogy is traditionally cultivated in schools through professional development. Though professional learning is common in all schools as a core practice, the design, quality, and results of the learning are unequal and inconsistent. Common practices such as lectured presentations, "sit and get" sessions, and brief "one-size-fits-all" workshops continue to be the most prevalent professional development methods used in schools. Use of these methods facilitates neither a change in teacher behavior nor an improvement in student performance. As a best practice, teachers require ongoing, personalized professional development that is designed and aligned with the tenets of effective andragogy to develop higher-order skills that are more likely to be transferred to classroom instruction. However, there exists a disconnect between professional development practices and the effective transfer of assumed learning. This transfer is essential in order to improve teaching practices. Only subsequent to this transference will changes in teaching and learning occur. In this study, a qualitative research design was used to determine whether personalizing professional development has an impact on instructional practices and change in teacher perception of professional learning. Using a model for personalized learning, this study found that, when school leaders implement such a model, positive changes in teacher instructional practices and attitudes towards professional learning resulted.
Keywords: personalized professional learning; Teachers--In-service training; Academic achievement; Professional learning communities